Agenda setting, localisation and the third-person effect: an experimental study of when news content will directly influence public demands for policy change. (2nd January 2018) - Jamieson, Thomas; Van Belle, Douglas A.
ABSTRACT: Building from the third-person effect model of DRR policy adoption and mediated policy learning, this study provides an experimental examination of how specific elements of news media's localisation of distant events directly influence public opinion. Controlling for salience effects, the construction of affinities between the distant, stricken community and the newspaper's audience is argued to create a sense of shared vulnerability to the reported disasters. This is correlated within an increase in the respondent's intention to act directly and an increase in their willingness to punish elected officials who do not act accordingly. The construction of difference between the communities, even though it is not related to risks related to the disaster, is argued to create implicit reassurances that the observing community does not need to act. This leads to an increased intention to act directly in opposition to efforts to reduce risk, but a neutral response towards political actors who pursue risk reduction policy actions.